2019
DOI: 10.1186/s40814-019-0517-3
|View full text |Cite
|
Sign up to set email alerts
|

Healthy Parent Carers peer-led group-based health promotion intervention for parent carers of disabled children: protocol for a feasibility study using a parallel group randomised controlled trial design

Abstract: BackgroundParent carers of disabled children are at increased risk of mental and physical health problems. They often experience challenges to maintaining good health which have implications for their well-being and their ability to care for their children. In response to these needs, researchers and parent carers developed the Healthy Parent Carers (HPC) programme. It is a peer-led, group-based intervention that promotes behaviours associated with health and well-being. The aims of this trial are to assess th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
6
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5

Relationship

3
2

Authors

Journals

citations
Cited by 5 publications
(6 citation statements)
references
References 47 publications
0
6
0
Order By: Relevance
“…The CONSORT reporting checklist is provided as an additional file (see Additional file 1). The methods were provided in detail in the protocol [23].…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…The CONSORT reporting checklist is provided as an additional file (see Additional file 1). The methods were provided in detail in the protocol [23].…”
Section: Methodsmentioning
confidence: 99%
“…Participants' use of health care, social care, and wider societal resources was measured using a studyspecific resource use questionnaire. Full details of the measures used are in the study protocol [23].…”
Section: Outcome Measuresmentioning
confidence: 99%
“…The feasibility study aimed to assess whether the programme could be delivered in the community and evaluated the acceptability of a randomised controlled trial (RCT) design. 23 The trial ran between July 2018 and June 2020. Ninety-two participants were randomised: 47 to the HPC group programme (delivered in six community sites across Cornwall, Devon and Somerset) and 45 to the control group, which involved access to the HPC online resources only.…”
Section: The Feasibility Studymentioning
confidence: 99%
“…The strength of this research is that it has systematically followed key principles of intervention development 27 28 and refinement using a dynamic, iterative and creative process with extensive stakeholder consultation, where the developers have been open to change based on data collected in a series of iterations. 22 23 We examined how the intervention will be evaluated in the next phase of research and identified learning and key uncertainties to be addressed, such as blended (online and face-to-face) delivery of group sessions, commissioning and implementation. Reporting mixed methods data on participant views and experiences and the subsequent refinement process in feasibility studies is recommended.…”
Section: Programme Refinementmentioning
confidence: 99%
“…The Family Faculty is made up of families containing children with disabilities who are living in the United Kingdom, and who are interested in the work being carried out by the Peninsula Childhood Disability Research Unit. 22,32 Members are invited to get involved in our research in a number of ways. 33 For example, they are encouraged to suggest research questions, get involved in project working groups, and make suggestions about the language we useincluding helping us to design plain language summaries.…”
Section: Patient and Public Involvement (Ppi)mentioning
confidence: 99%